Implementasi Undang-Undang No.18 Tahun 2013 Tentang Pencegahan Dan Pemberantasan Perusakan Hutan (Studi Kasus Tentang Faktor-Faktor Yang Mempengaruhi Masyarakat Melakukan Perambahan Hutan Di Desa Lunyuk Ode Kecamatan Lunyuk Kabupaten Sumbawa Besar) - Amil Amil; Taufik Rachman (JIAP (Jurnal Ilmu Administrasi Publik), 2018)
One of the causes of forest destruction is forest encroachment. The problem of forest encroachment has become a national problem. Several factors have caused the community to do forest encroachment, namely weak law enforcement, income factors, education factors, the existence of sponsors and the limitations of forest supervision officers. Increasing the number of residents resulted in an increase in the need for land to share interests. This increasing need threatens the existence of forests. The increasing need for land has resulted in increased forest clearance. Problems related to forest encroachment in Lunyuk Ode Village, Lunyuk Subdistrict, Sumbawa Besar Regency have caused researchers to be interested in conducting research with the title "Implementation of Law No. 18 of 2013 concerning Prevention and Eradication of Forest Destruction (Case Study of Factors Affecting Communities to Encroach Forest in Lunyuk Ode Village, Lunyuk Subdistrict, Sumbawa Besar Regency) ". The purpose of this research is to find out the factors that influence the community to do forest encroachment and what impacts are felt by the people of Lunyuk Subdistrict, Sumbawa Besar District from forest encroachment activities. The research method used is a qualitative method, because it examines reality, phenomena or symptoms that are holistic / intact. Data collection techniques are carried out by means of participatory observation and in-depth interviews and documentation techniques in the form of photographs. The informants in this study were selected using the snowball sampling technique. Data analysis is done qualitatively with three stages, namely data reduction, data display and conclusion. The conclusions that can be drawn from the results of this study are the factors that influence the community to do forest encroachment are; first, economic factors which include the high income of the community after carrying out forest encroachment activities due to the high selling price of timber and demand for timber and lack of employment. Second, a low education factor. Third, weak forest guarding factors. Fourth, a mild penalty factor so that people are not afraid to do forest encroachment.